Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia (IPM) dan Pengangguran terhadap Kemiskinan di Provinsi Nusa Tenggara Timur - Koja, Marlince Tara; Hudang, Adrianus Kabubu; Renggo, Yuniarti Reny (Jurnal Ilmiah Global Education, 2024)
Poverty is a challenge to development in various sectors characterized by deprivation, inability, and lack. People living in poverty often experience nutritional problems, poor health, high illiteracy rates, inappropriate environments, and limited access, both in rural and urban areas, such as in small poor villages or isolated seaside communities. This research is a quantitative study, which uses a statistical approach to test hypotheses. Specifically, this study analyzes the effect of Economic Growth, Human Development Index, and unemployment rate on the poverty rate in East Nusa Tenggara. Statistical analysis was conducted using panel data regression with the help of Eviews10 software processing. The results show that: the Human Development Index (HDI) has a significant effect on poverty in East Nusa Tenggara Province, while Economic Growth and Unemployment have no significant effect on the poverty rate in East Nusa Tenggara Province.